Epistemic configuration of pedagogy. Widespread trends in the history of education - Ortiz Ocaña, Alexander (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2017)
This article carries out a reflexive thematic review that allows to analyze the genesis, evolution, and epistemic configuration of the pedagogy by evaluating the main tendencies that have widespread in the history of education. Five tendencies or epistemological orientations are identified: pedagogy as a science of education, pedagogy as one of the sciences of education, pedagogy as pedagogical knowledge, pedagogy as the art of teaching (didactics), and pedagogy as a reflection on the education. Pedagogy is considered as the universal constellation of pedagogical knowledge configured by the international academic community. However, the controversial debate on pedagogy and the education sciences is still in force. There is no consensus within the international academic community about the epistemic configuration of pedagogy. The conceptions and criteria depend on the particularities of this science or discipline in each country. In Colombia, pedagogy is a pedagogical knowledge or a reflection on education; in Cuba, pedagogy is considered the science that studies education; in the United States it is the Science of Education, in singular, but it is not used the notion of pedagogy with the connotation of education science. Also, in France, they refer to the Sciences of the Education, in plural, and in Germany, the Pedagogy is understood as the Science of Education. It is concluded that pedagogy should not be considered as a field, but a comprehensive conceptual configuration.